Reaction of adult rats’ erythrocytes under gingivitis during respiratory hypoxia - V. F. Cheremisina (Journal of Education, Health and Sport, 2017)
Cheremisina V. F. Reaction of adult rats’ erythrocytes under gingivitis during respiratory hypoxia. Journal of Education, Health and Sport. 2017;7(1):468-477. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.321677